Descoberta e composição de serviços web semânticos através de algoritmo genético baseado em tipos abstratos de dados - Soares, Elvys Alves (2009)
The Semantic Web is an extension of the current Web, where the availability of information is expected to enable the cooperation between man and, above all, machines. The creation of standards which express shared meaning enable the construction of applications to solve integration, collaboration and automation problems which were already been identified by scientific community and technology consumers. The use of Web Services has brought several advances in this sense, and their annotation in semantic terms, transforming them into Semantic Web Services, enables the Semantic Web intent. Several technologies also enable the creation of such elements and their inherent use as basic blocks of application development whose scope is embedded on Web. This way, due to the fast growing of the number of services, some approaches to effectively solve the problem of services integration and use become necessary. This work proposes a modeling of a software solution to the discovery and composition of Semantic Web Services problem through the use of a genetic algorithm based on abstract data types. It is also proposed a tool implementation using OWL, OWL-S and OWL-S API languages and frameworks as well as the formal problem definition along with the scientific community expectations to the given solution.